Comprehensive Analysis of the Social and Economic Impact of Carbon Trading Programs in East Asian Countries: Comparative Study - Maulida, Savira; Aulia, Azra Nawal; Nurcahyani, Ratna Alfina; Hartadi, Najla Aulia; Muis, Afni Regita Cahyani (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
The purpose of this research is to carry out an in-depth investigation on the social and economic effects that carbon trading schemes have had on East Asian nations of various kinds. The purpose of this study is to evaluate the efficiency of carbon trading programs in East Asian countries by employing a comparative analysis. The study's primary objectives are to comprehend the variations in outcomes that occur across different countries and to find the most successful methods for carbon trading. An approach known as case study research is utilized in this study in order to promote a more nuanced understanding of the social and economic implications that carbon trading regimes have in a variety of settings. In order to evaluate the social ramifications of carbon trading, qualitative data will be collected, which will include community perspectives, environmental justice issues, and societal changes. Additionally, economic metrics such as gross domestic product, employment rates, and industrial growth will be studied. For the purpose of formulating climate policies that are more effective, equitable, and environmentally sustainable, the findings of the study can provide policymakers with significant insights. The paper also makes recommendations for future research directions, such as conducting longitudinal studies to evaluate the long-term social and economic repercussions of carbon trading programs, investigating the implications of carbon trading across different sectors, and incorporating the perspectives of stakeholders into future research. According to the findings of the study, carbon trading programs have major economic and social consequences. These programs include the creation of economic incentives for businesses or governments to reduce carbon emissions in an efficient manner, as well as the promotion of a societal atmosphere that is sympathetic to sustainable practices.